Compressed air massage: repeated treatment causes less muscle oedema than a single treatment - M. A. Gregory; M. Mars (South African Journal of Physiotherapy, 2007)
Compressed air massage is a new treatment modality that has been shown to cause skeletal muscle capillary dilation for up to 24 hours after a single treatment and significantly hastens healing of diabetic ulcers. This study compares the effect of one treatment of a single muscle group, with repeated treatments of several muscle groups.